Pengelolaan Lingkungan Berbasis Etnoekologi dalam Pembelajaran Ilmu Pengetahuan Sosial (Studi Kasus di SMP Negeri 4 Bae Kudus) - Nengrom, Lidia; Fatmawati, Noor (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2023)
This research focuses on the application of ethnoecology-based environmental management in social studies learning as well as students' understanding of ethnoecology-based environmental management. Research data was obtained using observation, interviews, documentation and questionnaire methods. The research was carried out at SMP Negeri 4 Bae, Kudus Regency, with informants from the school principal, social studies teacher and students. The research results show that: 1) ethnoecology-based environmental management in social studies learning has implemented two habits; namely morning exemplary activities in the form of morning pickets which are carried out before learning begins by students according to the picket schedule, as well as learning in nature in the form of planting activities, making drainage and managing waste which are tailored to learning outcomes; and 2) students' understanding of ethnoecology-based environmental management, including: aspects of wisdom, independence, religion, creativity and healthy living. Wisdom can be seen through the application of 3R (Reduce, Reuse and Recycle); independence through students being able to carry out class pickets without having to be instructed; Religious is seen from students being able to take advantage of the environment by upholding religious values; student creativity in managing used goods in craft activities or class competitions; and healthy lifestyle. With motivation and good examples from teachers, students will be created who understand and care about environmental management.